The Existence of The Islamic Student Association As an Agent of Social and Economic Change In The Framework of The Indonesian Legal State - Herman Rudiyansah, Muhammad Mas Davit; Fahruddin, Mohammad Arrozi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The existence of the Islamic Student Association (HMI) as an agent of social and economic change within the framework of the Indonesian State of Law. This study is motivated by the strategic position of student organizations in the history of the nation's journey which often appears as a moral force and social control over the direction of state policies. Using normative juridical methods enriched by conceptual and historical approaches, this study examines the constitutional legitimacy of student organizations, the relevance of HMI's role in socio-economic dynamics, and its conformity with the principles of the rule of law and democracy. The results of the study show that the existence of HMI has a strong normative basis in the principle of freedom of association and assembly, as well as gaining legitimacy as long as its activities are in line with constitutional values. Substantively, HMI's role as an agent of social change is reflected in the ideological, structural, and social pragmatic dimensions, while in the economic field, there is a transformation of the movement from a pattern of criticism to empowerment through strengthening entrepreneurship and community economic assistance. Despite facing internal challenges in the form of cadre consistency and external challenges in the form of social, political, and technological changes, HMI still shows adaptive capacity in maintaining its relevance. Thus, this study emphasizes that the existence of HMI is dynamic and contextual as part of civil society that plays a role in maintaining a balance between the state and society, as well as contributing to equitable social and economic development within the framework of the state of law.